Reviving the Spirit of Gender Equality: Fatayat Nahdlatul Ulama between Idealism and Realization - Aprilian Ria Adisti (Journal of Nahdlatul Ulama Studies, 2021)
As the Muslim women's movement Nahdlatul Ulama, Fatayat NU has dedicated itself especially to reviving the spirit of gender equality in society. This study uses a descriptive qualitative research design that portrays basic cadre training as an effort to strengthen the spirit of gender equality in Fatayat NU cadres. This research is conducted at the Budossyan Village Hall, Tengaran District, Semarang Regency, which was attended by 50 Fatayat NU cadres. The data collection instruments are observation, interview and documentation. Realizing idealism in gender equality requires hard work from all elements. Fatayat NU is actively empowering women to reach gender equality in society even though in reality they still face many challenges and obstacles. The biggest challenge faced by Fatayat NU is how to fight the patriarchal culture that still dominates women roles in society. The results shows that the implementation of this training is successful in supporting Fatayat NU cadres to be more sensitive to issues of gender inequality by encouraging themselves to take an important role in society. Finally, it is concluded that the realization of idealism in reviving the spirit of gender equality in Fatayat NU still needs to be improved and evaluated periodically so that Fatayat NU cadres can become role models as agents of change in society in achieving gender equality.